Impact of Leadership on Employee Behaviour and Attitude in The Ministry of Finance, Ghana - Snr , Atta Dabone (International Journal of Finance, 2024)
Purpose: This study investigates the influence of leadership on employee behaviour and attitude in the Ministry of Finance in Ghana. It specifically focusses on how leadership practices affect productivity in a public sector setting. The research investigates the adaptive qualities of leadership styles and their efficacy in meeting the varied demands of employees, based on the principles of Situational Leadership Theory (SLT). Methodology: The study utilises a descriptive survey method. The study population consists of all 628 employees of the Ministry, with a sample size of 246 determined through a multi-stage sampling process. Data is obtained by questionnaires. Findings: The findings suggest that leadership roles and practices have a moderate impact on employee behaviour and productivity. Leaders are seen as successful role models, but they are lacking in providing personalised support and effectively communicating goals. The effectiveness of leadership tactics is not considerably influenced by age. The study's findings suggest that implementing leadership development programs, improving communication methods, and providing individualised support mechanisms will promote organisational efficiency and employee engagement in the Ministry of Finance. Policy Implications and Recommendations: Ministries should develop and implement comprehensive training programmes for leaders that focus on enhancing role modeling, setting high performance expectations, and providing effective intellectual stimulation. Governmental ministries should introduce policies and practices that improve the communication of organizational goals and increase employee involvement in the goal-setting process.